2015
DOI: 10.1653/024.098.0316
|View full text |Cite
|
Sign up to set email alerts
|

A New Subspecies ofPierella lena(Lepidoptera: Nymphalidae: Satyrinae) in Northeastern Brazil

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…The Neotropical genus Pierella Westwood, 1851, so far, with four species in northeastern Brazil in the states Alagoas, Paraíba, Bahia and Pernambuco (Cardoso 1949;Kesselring & Ebert 1982;Zacca 2009;Paluch et al 2011;Zacca et al 2011), has revealed new taxa to the Northeastern Atlantic Forest, as Pierella sp. nov. in FLS described in Zacca et al (in press) (Taxonomic revision of the ''Pierella lamia species group''), as well as, Pierella lena atlantica Paluch, Zacca & Siewert, 2015in Paluch et al (2015.…”
Section: Resultsmentioning
confidence: 99%
“…The Neotropical genus Pierella Westwood, 1851, so far, with four species in northeastern Brazil in the states Alagoas, Paraíba, Bahia and Pernambuco (Cardoso 1949;Kesselring & Ebert 1982;Zacca 2009;Paluch et al 2011;Zacca et al 2011), has revealed new taxa to the Northeastern Atlantic Forest, as Pierella sp. nov. in FLS described in Zacca et al (in press) (Taxonomic revision of the ''Pierella lamia species group''), as well as, Pierella lena atlantica Paluch, Zacca & Siewert, 2015in Paluch et al (2015.…”
Section: Resultsmentioning
confidence: 99%
“…Haeterini butterflies were collected by the authors and collaborators throughout most of the geographical range of the tribe, including localities from northern Costa Rica to southeastern Brazil. Specimens were identified to the species and subspecies level following published taxonomic revisions (Constantino, 1995; Lamas, 1997; Penz et al , 2014; Paluch et al , 2015; Willmott, 2015; Zacca et al , 2016) and comparing wing morphology to type specimen photographs at https://www.butterfliesofamerica.com (last accessed August 2018). We sampled all five Haeterini genera, including 18 of 29 currently valid species, and 18 of 39 subspecies (Lamas, 2004; Penz et al , 2014; Paluch et al , 2015; Willmott, 2015; Zacca et al , 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Haeterini butterflies were collected by the authors and collaborators throughout most of the geographical range of the tribe, including localities from northern Costa Rica to southeastern Brazil. Specimens were identified to the species and subspecies level following published taxonomic revisions (Constantino, 1995;Lamas, 1997;Penz et al, 2014;Paluch et al, 2015;Willmott, 2015;Zacca et al, 2016) and comparing wing morphology with type specimen photographs at https://www .butterfliesofamerica.com (accessed August 2018). We sampled all five Haeterini genera, including 18 out of 29 currently valid species, and 18 out of 39 subspecies (Lamas, 2004;Penz et al, 2014;Paluch et al, 2015;Willmott, 2015;Zacca et al, 2016).…”
Section: Taxon Sampling and Molecular Datasetmentioning
confidence: 99%
“…Specimens were identified to the species and subspecies level following published taxonomic revisions (Constantino, 1995;Lamas, 1997;Penz et al, 2014;Paluch et al, 2015;Willmott, 2015;Zacca et al, 2016) and comparing wing morphology with type specimen photographs at https://www .butterfliesofamerica.com (accessed August 2018). We sampled all five Haeterini genera, including 18 out of 29 currently valid species, and 18 out of 39 subspecies (Lamas, 2004;Penz et al, 2014;Paluch et al, 2015;Willmott, 2015;Zacca et al, 2016). Note that several subspecies were not represented in our sample because they are only known from type collections (hampering their access for genetic studies) or have rarely been collected in recent years.…”
Section: Taxon Sampling and Molecular Datasetmentioning
confidence: 99%
See 1 more Smart Citation